Machine learning-based methods for TTF estimation with application to APU prognostics - Yang, Chunsheng; Letourneau, Sylvain; Liu, Jie; Cheng, Qiangqiang; Yang, Yubin (Applied intelligence (Dordrecht, Netherlands), 2017)
NRC publication: Yes